FGF3/FGF4 amplification and multiple lung metastases in responders to sorafenib in hepatocellular carcinoma1. Issue 4 (11th February 2013) - Arao, Tokuzo; Ueshima, Kazuomi; Matsumoto, Kazuko; Nagai, Tomoyuki; Kimura, Hideharu; Hagiwara, Satoru; Sakurai, Toshiharu; Haji, Seiji; Kanazawa, Akishige; Hidaka, Hisashi; Iso, Yukihiro; Kubota, Keiichi; et al.
Abstract The response rate to sorafenib in hepatocellular carcinoma (HCC) is relatively low (0.7%‐3%), however, rapid and drastic tumor regression is occasionally observed. The molecular backgrounds and clinico‐pathological features of these responders remain largely unclear. We analyzed the clinical and molecular backgrounds of 13 responders to sorafenib with significant tumor shrinkage in a retrospective study. A comparative genomic hybridization analysis using one frozen HCC sample from a responder demonstrated that the 11q13 region, a rare amplicon in HCC including the loci for FGF3 and FGF4, was highly amplified. A real‐time polymerase chain reaction–based copy number assay revealed that FGF3/FGF4 amplification was observed in three of the 10 HCC samples from responders in which DNA was evaluable, whereas amplification was not observed in 38 patients with stable or progressive disease (P = 0.006). Fluorescence in situ hybridization analysis confirmed FGF3 amplification. In addition, the clinico‐pathological features showed that multiple lung metastases (5/13, P = 0.006) and a poorly differentiated histological type (5/13, P = 0.13) were frequently observed in responders. A growth inhibitory assay showed that only one FGF3/FGF4‐amplified and three FGFR2‐amplified cancer cell lines exhibited hypersensitivity to sorafenib in vitro. Finally, an in vivo study revealed that treatment with a low dose of sorafenib was partially effective for stably and exogenously expressed FGF4 tumors, while being less effective in tumors expressing EGFP or FGF3. Conclusion: FGF3/FGF4 amplification was observed in around 2% of HCCs. Although the sample size was relatively small, FGF3/FGF4 amplification, a poorly differentiated histological type, and multiple lung metastases were frequently observed in responders to sorafenib. Our findings may provide a novel insight into the molecular background of HCC and sorafenib responders, warranting further prospective biomarker studies. (HEPATOLOGY 2013)